Observational Analysis of Popular Conception of Clientelism in Macedonia - Markovikj, Nenad & Gocevski, Dragan (Konrad Adenauer Stiftung & IDSCS, 2018)
The article examines qualitative data related to perceptions of the occurrence of clientelism in the Republic of Macedonia. Additionally, it examines the personal involvement in clientelist practices in various social spheres. The article analyses descriptive statistics (frequencies), with the aim to inform the reader on the current perceptions of clientelist practices and the involvement in clientelist practices in Macedonian society. The text also analyses the gap between the perceptions and the personal experience in different social spheres. It is based on quantitative data gathered through the project “INFORM: Closing the gap between formal and informal institutions in the Balkan.”
Keywords: clientelism, Macedonia, perceptions, involvement